"Mengapa Kamu Menaklukkan Dirimu pada Berbagai Peraturan?": Gagasan-gagasan dari Nietzsche untuk Menjadi Seorang Kristen yang Autentik - Katianda, Samuel Tesa (Indonesian Journal of Theology, 2025)
Although Friedrich Nietzsche is known for his critical stance on Christianity, his philosophy can offer valuable insights for examining Christian life. Building on Merold Westphal’s assertion that Nietzsche’s philosophy might contribute to Christian theology, this paper demonstrates that Nietzsche’s ideas can aid Christians in pursuing authenticity by encouraging them to question established traditions. This paper explores Nietzsche’s critique of morality and Christianity, his concept of authenticity, and provides a theological analysis of Nietzsche’s thought.